Bibliometric Analysis of Scientific Production on Agricultural Cooperatives in Spanish-speaking Countries. - Camacho-Bercherlt, Mirna; Rojas Herrera, Juan José; Santillán Fernández, Alberto (Cooperativismo & Desarrollo, 2023)
Agricultural cooperatives are social enterprises dedicated to the production, transformation and marketing of agricultural, livestock and forestry products. Its business-associative model is little known due, among other causes, to its scarce diffusion in printed media of a scientific nature. For this reason, the objective of this research was to analyze the spatio-temporal evolution of scientific production on agricultural cooperatives in Spanish-speaking countries, through a bibliometric analysis that would allow identifying the main countries, topics and scope of publications. We collected 164 scientific articles published between 2001 and 2021, in which the spatio-temporal evolution of the research showed a linear growth (R2=0.47, P
Keywords: bibliometric analysis; agrarian cooperatives; agricultural cooperatives; crop and livestock cooperatives; rural cooperatives